Significance of Educational Methods in Shaping Graduates’ Competencies in Belarus - Navarro-Milla, Isidora; García-Aracil, Adela; Isusi-Fagoaga, Rosa (Journal of Teaching and Learning, 2026)
This paper analyses higher education graduates’ feedback on how teaching and learning methods enhance competencies. The analysis focuses on Belarus and uses data from the Fostering Competencies Development in Belarusian Higher Education (FOSTERC) survey, an online survey of 5443 young graduates conducted in 2018. The survey gathered information on 12 items related to educational methods and 24 competencies emphasized in graduate study programs. Factor analysis allowed us to group these 24 competencies into two categories: entrepreneurial and transversal. We also considered other variables, such as graduate characteristics and contextual factors. Our results indicate that, overall, the most common teaching-learning method in Belarusian study programs is the traditional lecturer-led approach, with the teacher as the main source of information. However, graduates exposed to more active teaching-learning methods reported that these methods positively influenced the development of entrepreneurial and transversal competencies. We observed gender stereotypes related to study fields: female graduates in education sciences (compared to male peers) had a more positive perception of their study programs in terms of promoting entrepreneurial and transversal competencies. This finding raises concerns, as courses in the natural sciences, engineering, and social sciences have traditionally been considered more likely to produce future entrepreneurs and innovators.